Формування та імплементація системи аграрного маркетингу в діяльність аграрних підприємств - Багорка, Марія Олександрівна; Bahorka, Mariia; Кравець, Ольга Василівна; Kravets, Olga (Міжнародний університет бізнесу і права, 2024)
В статті розглянуто дефініції щодо поняття «аграрний маркетинг», виявлені проблеми в аграрній сфері бізнесу, надано організаційно-методичне обґрунтування ведення маркетингової діяльності в агробізнесі на рівні держави, регіонів, підприємств та сформовані складові системи аграрного маркетингу для імплементації в діяльність аграрних підприємств. У результаті дослідження встановлено, що у переважної більшості сільськогосподарських підприємств організаційна структура не відповідає принципам маркетингу, що проявляється в складності внутрішньої взаємодії служб і відділів, обмежених маркетингових інструментах аналізу ринку, неефективному управлінні. Запропоновано впровадження маркетингово-орієнтованої організаційної структури аграрних підприємств для оптимізації взаємовідносини між службами та підрозділами підприємства, та використання інструментів маркетингу для дослідження ринку. Рекомендовано в сучасних умовах здійснювати продажі максимально використовуючи мережу Інтернет, тобто цифрову платформу, що допомагає оптимізувати фінансові, трудові та виробничі ресурси та витрати. The article considers the definitions of the concept of "agricultural marketing", identified problems in the agrarian sphere of business, provided an organizational and methodological rationale for conducting marketing activities in agribusiness at the level of the state, regions, and enterprises, and formed the components of the agrarian marketing system for implementation in the activities of agrarian enterprises. Agricultural marketing can be defined as a set of interdependent organizational, technical, financial and commercial functions of the enterprise, aimed at ensuring the sale of agricultural products in accordance with consumer requests for the benefit of the enterprise. The main goal of agricultural marketing is to fully satisfy the rational standard of food consumption by the population while ensuring the effective activity of agribusiness entities. An effective marketing system uses market analysis to predict demand; will try to minimize blind entry into markets and instead promote a withdrawal regime. Increases income – a well-organized marketing system will increase the total amount of income received in the agricultural value chain. The agricultural marketing system contains a set of the most important market relations and information flows that connect the agricultural enterprise with the markets. As a result of the study, it was established that the organizational structure of the vast majority of agricultural enterprises does not correspond to the principles of marketing, which is manifested in the complexity of the internal interaction of services and departments, limited marketing tools for market analysis, ineffective management. It is proposed to introduce a marketing-oriented organizational structure of agricultural enterprises to optimize the relationship between services and divisions of the enterprise, and to use marketing tools for market research. It is recommended in modern conditions to make sales using the Internet as much as possible, that is, a digital platform that helps to optimize financial, labor and production resources and costs.
Formation and implementation of the agricultural marketing system in the activities of agricultural enterprises
Keywords: аграрний маркетинг; аgricultural marketing; комплекс маркетингу; marketing complex; аграрна продукція; agricultural products; аграрні підприємства; agricultural enterprises; маркетинговий інструментарій; marketing tools; канали збуту; sales channels; середовище організації; organizational environment